Trends and topics in occupational diseases over the last 60 years from PubMed - Gehanno, Jean-Francois; Postel, Aurore; Schuers, Mathieu; Rollin, Laetitia (Scandinavian Journal of Work, Environment & Health, 2018)
' ' OBJECTIVES ': 'The purpose of this study was to provide an analysis of scientific production on occupational diseases (OD) during the period 1945–2015 in order to describe publication trends on that topic and identify the major diseases as well as the predominant actors (journals, countries) involved in this field. ' ' METHODS ': 'A PubMed search was carried out to extract articles related to occupational diseases during the period 1 January 1945 to 31 December 2015 using a specific query. Data were downloaded from PubMed in Extensible Markup Language (XML) and processed through a dedicated parser. ' ' RESULTS ': 'A total of 160 025 articles were retrieved from 7127 journals. One third of these articles were published in 39 journals: the core journals according to Bradford’s law. Following exponential growth, OD publications reached a plateau in 2007. The overall dynamics of the OD field are heterogeneous with differences between subfields: psychological diseases emerged in the 1990s while “traditional” OD are less studied nowadays. Despite a sharp decrease in the proportion of publications, the most productive country remains the USA with 14.5% of the OD publications over the period but Scandinavian countries are, proportionally, the most active in research and publication on OD. ' ' CONCLUSIONS ': 'The proportion of publications on OD is decreasing in Medline, except for specific subfields of OD. This is discrepant with the global burden of occupational diseases.
Keywords: bibliometrics; biomedical research; biomedical trend; occupational disease; publication; PubMed; trend